In silico genome-scale modeling and constraint-based analysis of microorganisms for bioelectricity generation and electrosynthesis. - Mao, Ning. (2013)
Systems biology offers great tools for genetic designs in metabolic engineering. Microorganisms' metabolic networks can be reconstructed into mathematical models and such models can be modified and evaluated through constraint-based analysis. Such in silico modeling and analysis promise a more systematic approach in the metabolic studies, thus saving a lot of laboratory efforts with more reliable designs.